Pengaruh Negara Asal Terhadap Keputusan Pembelian Mie Neoguri Di Mandiri Express Mart Medan - Saragih, Rena Uthami; Alfifto, Alfifto (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
To find out and analyze the influence of country of origin on the decision to purchase NeoGuri noodles at Mandiri Express Mart Medan. To find out and analyze the influence of halal labels on purchasing decisions for NeoGuri Noodles at Mandiri Express Mart Medan. To find out and analyze the country of origin and halal label which simultaneously influence the decision to purchase NeoGuri noodles at Mandiri Express Mart Medan. This research uses associative research, namely research that aims to determine the relationship between two or more variables, where the variables are measured using a Likert scale. This research used a sample of 65 Mandiri Medan Supermarket consumers. Based on the research results, it was concluded that simultaneously, Country of Origin and Halal Label had a positive and significant effect on the Purchase Decision for NeoGuri Noodles from Korea at Mandiri Express Mart Medan. Partially, Country of Origin and Halal Label have a positive and significant effect on the Purchase Decision for NeoGuri Noodles from Korea at Mandiri Express Mart Medan. Based on the Adjusted R Square calculation of 0.722, it means that 72.2% of the variation in purchasing decision factors can be explained by the Country of Origin and Halal Label variables. Meanwhile, the remaining 27.8% can be explained by other factors not included in this study.